Quatro clics em Paulo Leminski - Rafael Fava Belúzio (2019)
This thesis analyzes and conveys four ways of syntheses developed in the literary works of Paulo Leminski. Chapter 0: nothing but a click. Chapter 1: a brief theoretical concept on Opening poem [Poema de abertura]. Chapter 2: an overview of the approaches concerning the Leminskian synthesis achieved by literary criticism; and a discussion, based on the interpretation of the opening poem contranarciussus [contranarciso], about how Leminski both revisits the Christian notion of the Triune God and elaborates syntheses that are independent in their differences and equal in their unity. Chapter 3: analyses of other works of the writer such as the novel Catatau, the biographies compiled in Life [Vida] and the essay Metaformosis [Metaformose]. This chapter also includes a reading of a letter-poem in which the author positions himself as a capitalist communist; a development of a biographical appreciation of a couplet; and an investigation on Noucentist, Oriental and Franciscan sources of a haiku. Thus, this thesis tries to analyze and express the Zero, the Brief, the Pair and the Reunion of the Diverse that constitutes the four syntheses in Paulo Leminskis work.